KRITISI SISTEM PERTANGGUNG JAWABAN NEGARA ATAS PERBUATAN MELAWAN HUKUM STUDI PERBANDINGAN ACTIO POPULARIS DI HUNGARIA - Halomoan Benarivo; Putri Purbasari Raharningtyas; Febiana Rima Kainama (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2021)
Citizens' lawsuits or commonly referred to as Citizen Lawsuits or Actio Popularis are the main access for citizens to sue the government because of their negligence in making decisions that result in unlawful acts committed by the government. In Indonesia, this lawsuit is not familiar to the public because actually this lawsuit is growing rapidly in the common law system country, but due to several things, Indonesia has finally implemented this. In fact, this lawsuit is also developing in Civil Law countries, for example Hungary, but because it is not as popular as in the United States as a common law system, Indonesia finally uses the term applied in common law countries, namely citizen lawsuit and does not use the term developed in civil law countries, namely action popularis. As a result, citizen lawsuits that develop in Indonesia are far from perfect, and often result in misunderstandings or misinterpretations and lead to inappropriate judges' decisions.